Apatite and zircon compositions for Miocene mineralizing and barren intrusions in the Gangdese porphyry copper belt of southern Tibet: Implication for ore control - Li, Qiang; Sun, Xiang; Lu, Yongjun; Wang, Fangyue; Hao, Jinhua (Ore geology reviews, 2021)
[Display omitted] •Gangdese Miocene fertile and barren adakite-like intrusions share similar ΔFMQ values and apatite S concentrations.•Variations of apatite Cl and S concentrations from core to rim indicate fluid exsolution in fertile and barren rocks.•Some barren porphyries have higher apatite/melt Cl concentrations than the fertile intrusions.•Enrichment of melt Cl and S alone is not critical to forming economic porphyry copper mineralization.•Caution must be taken when applying compositions of detrital zircon and apatite grains to ore prospecting. Gangdese porphyry copper belt in southern Tibet of China contains many Miocene fertile and barren adakite-like intrusions. Their magmatic oxidation state and volatile concentrations were poorly constrained. Here, we present apatite and zircon composition data for the Miocene fertile intrusions in the Qulong, Jiru, and Zhunuo porphyry copper deposits, and the coeval barren porphyries at Yare, Mayum, and Lasa in the Gangdese belt. Magmatic zircons of intrusions from the six locations share similar ΔFMQ (FMQ represents the reference buffer fayalite + magnetite + quartz) values, indicating both fertile and barren rocks have similar magmatic oxidation state. Variations of apatite Cl concentrations and characteristics of S- and Cl-rich core to abruptly S- and Cl-poor rim at Qulong, Jiru, Zhunuo, Yare, and Mayum are indicative of fluid exsolution from vapor-saturated magma. In contrast, fluid exsolution was not recognized from the available apatite composition data at Lasa which are characterized by constant or increasing apatite Cl concentrations with decreasing F/Cl ratios from core to rim. Some apatites at Lasa have high SO3 concentrations at the core compared with the rim, which would be attributed to early crystallization from S-rich magma followed by crystallization of sulfate minerals in a vapor-undersaturated magma. Some apatites from the fertile intrusions at Qulong, Jiru, and Zhunuo have lower Cl concentrations than those from the barren rocks at Yare, Mayum, and Lasa, which is consistent with the observation from the calculated melt Cl concentration. In addition, the SO3 concentrations at the core of apatites from all the fertile rocks are overlapping with those from all the barren rocks. Therefore, enrichment of Cl and S alone in melts may not be critical to forming economic porphyry copper mineralization in the Gangdese belt. Cautions must be taken when using compositions of detrital zircon and apatite grains to evaluate metallogenic potential during regional geochemical surveys.